How the nursing work environment moderates the relationship between clinical judgment and person-centered care among intensive care unit nurses. - Mi Hwa Seo; Eun A Kim; Hae Ran Kim (PLoS ONE)
Background Person-centered care focuses on individualized care that respects patients' values, preferences, and autonomy. To enhance the quality of critical care nursing, institutions need to identify the factors influencing ICU nurses' ability to provide person-centered care. This study explored the relationship between clinical judgment ability and person-centered care among intensive care unit (ICU) nurses, emphasizing how the ICU nursing work environment moderates this relation. Methods A cross-sectional survey was conducted between September 4 and September 18, 2023, with 192 ICU nurses recruited from four general hospitals with a convenience sample (valid response rate = 97.4%). Participants completed online self-report structured questionnaires. The collected data were analyzed using hierarchical multiple regression and PROCESS macro Model 1, with a 95% bias-corrected bootstrap confidence interval to verify moderating effects. Results Clinical judgment ability (β = .24, p < .001) and ICU nursing work environment (β = .50 p < .001) were found to be significant predictors of person-centered care. These two predictors explained the 47.0% of person-centered care in the final hierarchical regression model. Additionally, Clinical judgment (B = 0.28, p < .001, Boot. 95%CI = 0.13~0.42) and the ICU nursing work environment (B = 0.41, p < .001, Boot. 95%CI = 0.30~0.52) positively affected person-centered care, and the interaction term of clinical judgment and ICU nursing work environment (B = 0.16, p = .026, Boot. 95%CI = 0.02~0.30) also positively affected person-centered care. The moderating effect was particularly significant when the ICU nursing work environment score was 2.90 points (below 14.6%, above 85.4%) or higher on a scale of 1-5 and As the ICU nursing work environment score increased, the positive moderating effect also increased. Conclusions The ICU nurses' clinical judgment ability positively affected person-centered care, and the nursing work environment moderated the relationship between clinical judgment ability and person-centered care. Therefore, strategies for enhancing person-centered care among ICU nurses should focus on developing educational programs to improve clinical judgment ability and implementing comprehensive efforts to effectively improve and manage the nursing work environment.